Hygroscopic behavior and morphological characteristics of okra powder obtained by convective drying - Santos, Francislaine Suelia dos; Feitosa de Figueirêdo, Rossana Maria; de Melo Queiroz, Alexandre José; Romão Silva, Luis Paulo Firmino; Reis, Carolaine Gomes; Lima, Thalis Leandro Bezerra (Comunicata Scientiae, 2021)
Okra is a vegetable that stands out agronomically due to its fast growing cycle of high yield, in addition to considerable nutritional and commercial value. Due to its composition and because it is still consumed green, its shelf life in natural form is short. The objective of this work was to evaluate the hygroscopic, morphological and physical behavior of okra powders obtained in convective drying at different temperatures. The okra was cut into approximately 2 mm slices and dried in an oven with forced air circulation at temperatures of 50, 60, 70 and 80 ° C, with regular weighing until hygroscopic balance was reached. Then, the hygroscopic behavior of the powders was evaluated using water adsorption isotherms at a temperature of 25 ° C and mathematical models of GAB, Peleg, Oswin, Halsey and Henderson were adjusted to the experimental data. The powders were also submitted to morphological analysis by scanning electron microscopy (SEM) and X-ray diffraction analysis. The results showed that all models were well adjusted to the isotherms of okra powders, with emphasis on the GAB model, with determination coefficients (R2)> 0.99 and average percentage deviations (P) <5%; isotherms were classified as type II, typical of products with a large amount of sugar and solutes and with low adsorption. From the physical analysis, it was concluded that the powders presented morphologically irregular, asymmetrical structures with amorphous characteristics.